Resignification in peruvian operatic production: social and political criticism in Verdi’s Alzira - Macalupú Cumpén, Pablo (2020)
In recent decades, opera programming in theaters around the world has demanded producers to explore new ways to represent traditional repertoire and others that not belong to the lyrical standard. In this creative exercise, cultural managers and stage directors seek to present, from opera, a performance that surpasses its entertainment functions and aesthetic enjoyment, and aim to offer a political and social discourse through it. In some cases, resignification process reach high levels of experimentation and innovation as it happened in the Verdi Festival in Parma in 2007 or, in other cases, emerges to report problems of today’s society through works that has been interpreted differently by previous generations as is the case of gender violence in Carmen, by Bizet. In this paper, we review the current trends in Latin America and Europe to interpret an opera from the stage direction. As main theme, we analyze the production of Giuseppe Verdi’s Alzira, by Jean Pierre Gamarra, presented in 2018 at the Gran Teatro Nacional. In that sense, we propose to debate to what extent an art such as opera can be the trigger for social, critical and academic debate on current affairs.